Menggemakan Suara Para Nabi pada Zaman Ini - Purwahadiwardaya, Al. (Jurnal Orientasi Baru, 2013)
The most important mission of a community called Church today remains in discerning the will of God and being a prophet who speaks God’s word, a priest who sanctifies and a shepherd or king who cares. This missionary call should in turn be the mission of the people of God and all baptized Christians as community as well as individual. How do we exercise our prophetic ministry today? Which of God’s plans of salvation is urgently to be delivered for the betterment of our society and our world today?